Suggestions for a better tertiary physical education experience: insights from students at a rural state university - Tagare, Jr., Ruben L.; Orfrecio, Marlene E.; Sumera, Eduard S.; Mancera, Marlon A.; Calixtro, Marichu A.; Janito, Cheeze R.; Lopez, Helen Grace D.; Dagoc, Priscilla P. (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study explored the concerns and suggestions of generation Z students in rural communities to improve the newly implemented tertiary physical education (PE) program in the Philippines - physical activity towards health and fitness (PATHFit). Employing a qualitative-ethnographic approach, data were gathered from 20 generation Z students who were selected and participated in purposive interviews using open-ended questions validated by experts. The findings highlighted several themes following the data analysis using the Colaizzi method: PE should be engaging and fun, moving beyond traditional books and materials; a more flexible curriculum is needed, one that does not feel like a rigid prescription; student-centered activities should be prioritized to promote active involvement; lectures should be limited, with a greater focus on interactive, hands-on experiences; access to sports equipment through a borrowing system is crucial for student participation; and high-quality teaching, characterized by clear communication and practical demonstrations, is essential for a more meaningful learning experience. The study concludes and implies that generation Z students in rural communities desire a more engaging, flexible, and interactive PATHFit program that aligns with their interests and needs. Their insights provide valuable direction for enhancing the curriculum, promoting active student involvement, and ensuring that teaching is clear, practical, and engaging.